Madrasah Reposition in Building Community Trust in Covid-19 Era Disruption - Ahmad Salim; Muh Mustakim (AT-TA'LIM, 2021)
The advancement of information systems is an opportunity and a challenge as well as for Islamic educational institutions. One of them is a madrasah. If madrasah does not respond appropriately and wisely to this progress, madrasah will be left behind and even abandoned. Thus, in simple terms the era of "disruption" has been described by many recent scientists. In addition, the Covid-19 pandemic has implications for human life, including education. Online learning is a necessity. How has madrasah responded toward two major phenomena in the past of year. This study used a qualitative method with a case study approach. The primary data sources came from the research locus, namely MI Maarif Kokap and MTsN 4 Kulon Progo. Data collection techniques are carried out through interviews, documentation and interviews. Meanwhile, data analysis adopted a triangulation system. The results of the study describe that the two madrasahs carried out five strategic steps in building community trust, namely (1) following the dynamics of the community, (2) making learning innovations, (3) involving the surrounding community, (4) assigning offline learning under certain conditions and (5) home visit activity. These findings show that in building public trust during the pandemic and disruption era, madrasahs need to be open to existing technological developments, follow community dynamics and strengthen relationships with Â Â stakeholders.